Application Of The Weber’s Verstehen Approach In Victimology Studies: With Reference To Structural Violence Against Women - Jasleen Kewlani Rambani (International Journal of Psychosocial Rehabilitation, 2020)
A considerable part of the present philosophy is covered by feminist theories and perspectives. The feminist perspectives developed within the framework of the times, when theorists and social scientists designed their ideas into patterns of theories and thoughts. Beginning from dominating paradigms of thought like Marxian and Socialist Feminism, academia refers to Radical Feminism; Liberal Feminism; Black Feminism and Eco-feminism in both empirical and doctrinal ways. There has been adequate research on the existing notional frameworks and much more is going on too. What lacks in any good analytical research is lack or absence of incorporation of the understanding of the changes that have occurred in socio-cultural, legal, political and institutional structures. This is exactly, what has happened in ‘Gender and Victimology Studies’. Women today cannot be seen as a single community; the concept of community has to be diversified and then understood. Sociological appropriation of community visualizes number of persons having common traits, socio-cultural set ups; emotional orientations; and issues too. Women today are not thus, a single community; they are diversified in nature, approaches, social traits and life situations. Even in a single unit like family or marriage two or more women do not share common existential features. The differences can be imagined and interpreted in case of rural-urban dichotomy; education and literacy; disease burden, medical care and support; and the like. The proposed paper intends to understand and elaborate the factors which divide women into different sub-communities within the women community. Following this, the work shall make an attempt to understand and explain how the theoretical approach of ‘verstehen’ propounded by Max Weber can be applied to undertake research and analysis in the realm of gender studies, especially in understanding victimization of women. Bias does not come in the arena of research options for sure, but ‘Subjective Interpretation’, that is ‘Verstehen’, can be one tool which can bring out the most objective results and findings. Secondary sources of information shall be used to work on this piece of research. However, during the development of the paper, if need is realized, some people shall be interviewed. On the whole, the paper shall be an interdisciplinary study to strengthen the application of subjective interpretation while understand victimization of women.